Multifaceted Roles of the KEAP1–NRF2 System in Cancer and Inflammatory Disease Milieu - Harit Panda; Huaichun Wen; Mikiko Suzuki; Masayuki Yamamoto (Antioxidants, 2022)
In a multicellular environment, many different types of cells interact with each other. The KEAP1–NRF2 system defends against electrophilic and oxidative stresses in various types of cells. However, the KEAP1–NRF2 system also regulates the expression of genes involved in cell proliferation and inflammation, indicating that the system plays cell type-specific roles. In this review, we introduce the multifarious roles of the KEAP1–NRF2 system in various types of cells, especially focusing on cancer and inflammatory diseases. Cancer cells frequently hijack the KEAP1–NRF2 system, and NRF2 activation confers cancer cells with a proliferative advantage and therapeutic resistance. In contrast, the activation of NRF2 in immune cells, especially in myeloid cells, suppresses tumor development. In chronic inflammatory diseases, such as sickle cell disease, NRF2 activation in myeloid and endothelial cells represses the expression of proinflammatory cytokine and adherent molecule genes, mitigating inflammation and organ damage. Based on these cell-specific roles played by the KEAP1–NRF2 system, NRF2 inducers have been utilized for the treatment of inflammatory diseases. In addition, the use of NRF2 inducers and/or inhibitors with canonical antineoplastic drugs is an emerging approach to cancer treatment.